Prediction the durability of thermoplastic adhesive wood joints by means of mathematical modelling - Кшивецький, Б.Я. (Problems of Tribology, 2014)
This paper presents results of the study concerning the prediction of durability of thermoplastic adhesive oak-wood joints by means of mathematical modelling. The results have been analyzed to establish the patterns of durability changes as a function of cyclic variation in moisture content and ambient temperature.The method of predicting the durability by means of mathematical modelling differs from the existing techniques in that the model provides a possibility of predicting the durability of adhesive wood joints with rather a high degree of accuracy, also this method takes less amount of time to make prediction without destruction the test wood adhesion joint. The results obtained make it possible to choose and recommend optimal service condition and also to influence the physical and mechanical proportion of thermoplastic adhesive wood joints.